Molecular Characterization of 12 Mango Germplasm Using RAPD markers (Plant Tissue Culture and Biotechnology, 2010)
Randomly amplified polymorphic DNA (RAPD) markers were used for the genetic variation and relationship analysis among 12 Mango (Mangifera indica L.) germplasm. Five oligonucleotide primers were employed to amplify DNA from 12 cultivars. PCR amplification with five primers generated 45 reproducible, clear and distinct bands, out of which 41 bands are considered polymorphic and the remaining four fragments (8.88%)  monomorphic. The size of amplified product ranged from 200 (RPI-5) to 3000 base pairs (RPI-1) with an average of nine bands per primer. The average polymorphism in all the 12 cultivars using the five primers was found to be 91.91%. Among all the primers RPI-2 and RPI-4 have shown 100% polymorphism while RPI-5 was found to be least polymorphism (81.81%). One specific band, namely was found with RPI-5, in a particular variety, Chiratpuri. The UPGMA (Unweighted Pair Group Method of Arithmetic Mean) dendrogram based on Jaccard’s similarity coefficient segregated the 12 mango germplasm into two clusters. Langra, Chiratpuri, Pravasankar, Alphanso, Sindhu and Kesar formed one cluster and rest six mango germplasm grouped together into another cluster. Sindhu and Alphanso cultivar pair was very close to each other with highest similarity coefficient (0.78), which was comparatively higher than all other cultivar pairs. On the other hand, Pravasankar and Neelam cultivar pair was more distinct to each other with the lowest intervarietal similarity coefficient 0.38. This study showed clearly that cultivars from Orissa unveiled maximum diversity and indicated the potential of RAPD markers for the identification of management of mango germplasm for breeding purposes.  Key words: Molecular characterization, Mango germplasm, Dversity  D.O.I. 10.3329/ptcb.v20i1.5972 Plant Tissue Cult. & Biotech. 20(1): 91-99, 2010 (June)